What Drives Foreign Direct Investments in Indonesia? - World Bank (World Bank, Washington, DC, 2018)
This note identifies some of the main determinants of foreign direct investments (FDI) to Indonesia, focusing in particular on the role of economic policies. To that end it develops a novel empirical analysis on the effects of various provisions in Indonesia’s Negative Investment List (DNI) on planned FDI inflows. It also assesses the impact of Bilateral Investment Treaties (BITs) and specific trade policy actions on FDI inflows to Indonesia. The results suggest that restrictions on foreign equity limits, investment locations, on the size of investors and the types of licenses required all deter planned FDI, with the first two having the strongest effects. The analysis also suggests that terminating a BIT reduces substantially FDI inflows from the affected country and that trade policy can also play an important role in attracting FDI. On the basis of the results of the analyses and the existing empirical evidence, the note draws some policy suggestions to increase FDI inflows to Indonesia.